Does Fintech Stimulate the Financial Performance and Stability of the Too-Big-to-Fail Banks? - Chhering, Mangal; Goel , Shweta (International Journal of Economics and Financial Issues, 2025)
This study investigates whether FinTech stimulates the financial performance and stability of Domestic Systemically Important Banks (DSIBs) in India. The objective of this study is to analyse the impact of financial technology on the financial performance and financial stability of systemically important banks, commonly referred to as too-big-to-fail banks. Employing regression analysis and robustness tests, the findings reveal a significant but negative impact of FinTech on both financial performance (return on assets) and financial stability (ZSCORE). A positive correlation between ROA and financial stability suggests that more profitable banks tend to be financially stable. This research contributes to understanding the complex role of FinTech in shaping the financial health of systemically important banks in emerging economies. The study acknowledges limitations related to data scope, model assumptions, and sector focus, and calls for future research on long-term stability, cross-country comparisons, and the impact of emerging technologies such as AI and blockchain.